Caracterización basada en ECG de la extensión, gravedad y ubicación espacial de la isquemia aguda - Rodríguez-Carbó, Jimena; Pueyo Paules, Esther; Mincholé Lapuente, Ana (Jornada de Jóvenes Investigadores del I3A, 2024)
The aim was to quantify changes in ventricular depolarization and repolarization during acute myocardial ischemia using electrocardiogram. The results showed that there is a temporal evolution in the morphologies of the QRS and T waves during ischemia with a greater magnitude of change in repolarization.